Beyond the Asian crisis pathways to sustainable growth - Chowdhury, Anis 1954-; Islam, Iyanatul 1953- (Cheltenham, UK Northampton, MA Edward Elgar, 2001)
As Southeast and Northeast Asia recover from the Asian crisis and return to a state of growth, the authors of this book assess the lessons to be learned from the crisis to achieve sustainable development in the future. While the importance of each factor contributing to the crisis varies from country to country, their collective experience has created unprecedented turmoil in current thinking on development policy.
Includes bibliographical references and index.
Keywords: Sustainable development -- Asia; Financial crises -- Asia; Asia -- Economic policy; Asia -- Economic conditions -- 1945-.